2021
DOI: 10.1002/cpe.6821
|View full text |Cite
|
Sign up to set email alerts
|

False positive repression: Data centric pipeline for object detection in brain MRI

Abstract: One of the problems that often arise during the application of medical research to real life is the high number of false positive cases. This situation causes experts to be warned with false alarms unnecessarily and increases their workload. This study proposes a new data centric approach to reduce bias-based false positive predictions in brain MRI-specific medical object detection applications. The proposed method has been tested using two different datasets: Gazi Brains 2020 and BraTS 2020, and three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Gazi Brains 2020 is a new brain MRI dataset generated to meet the needs for qualified MRI datasets. Although a few studies have started to use this dataset [ 26 , 27 , 28 ], it was used for the first time for the in-domain TL. In this study, slices from 50 patients with HGGs were used.…”
Section: Methodsmentioning
confidence: 99%
“…Gazi Brains 2020 is a new brain MRI dataset generated to meet the needs for qualified MRI datasets. Although a few studies have started to use this dataset [ 26 , 27 , 28 ], it was used for the first time for the in-domain TL. In this study, slices from 50 patients with HGGs were used.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset preparation process is visualized in Figure 1 . The same dataset preparation process was performed as proposed by Terzi et al [ 45 ]. Accordingly, each independent mask was defined as an object in a slice.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…7 Ramazan It has been observed that the proposed pipeline is a promising solution to reducing FP cases. 8 The guest editors hope that the research contributions and findings in this special issue would benefit the readers in enhancing their knowledge and encouraging them to work on various aspects of intelligent systems and applications.…”
Section: Editorialmentioning
confidence: 99%
“…FPR‐P is proposed within the scope of the study by comparing with the classical pipeline by two different datasets as Gazi Brains 2020 and BraTS 2020, and three different deep learning models, as Mask R‐CNN, EfficientDet, and YOLOv5. It has been observed that the proposed pipeline is a promising solution to reducing FP cases 8 …”
mentioning
confidence: 99%